Analysis of Factors Affecting Hospital Risk Management in Indonesia: The SEM-PLS Approach - Dihartawan, Dihartawan; Lestari, Fatma; Widanarko, Baiduri; Besral, Besral (Kesmas, 2024)
Healthcare workers, especially those in hospitals, face a variety of complex hazards and exposures. One of the essential aspects of reducing risks and dangers is effective risk management. This study used a cross-sectional approach to survey the implementation of occupational health and safety management systems in Indonesian hospitals and to identify factors predisposing hospital risk management in Indonesia. A purposive sampling method was employed to select 90 hospitals distributed across 10 provinces in Indonesia. Data were analyzed using descriptive analysis, correlation, and SEM-PLS. A total of 44 hospitals (48.9%) had complete status plenary, and the majority were type C hospitals (43.3%). The results of SEM-PLS analysis showed that the hazard and risk identification analysis and Standard Operating Procedures (SOPs) factor-variables significantly predisposed the high quality of hospital risk management in Indonesia, with path values of 0.282 and 0.469, respectively. Enhancing hospital risk management in Indonesia could be achieved by increasing the use of appropriate SOPs and conducting a thorough analysis of hazards and risk identification.